Long-term variability, extremes and changes in temperature and hydrometeorology in the Amazon region: A review - Marengo, Jose Antonio [UNESP]; Espinoza, Jhan-Carlo; Fu, Rong; Jimenez Muñoz, Juan Carlos; Alves, Lincoln Muniz; DA ROCHA, Humberto Ribeiro; Schöngart, Jochen (FapUNIFESP (SciELO), 2024)
This review discusses observed hydroclimatic trends and future climate projections for the Amazon. Warming over this region is a fact, but the magnitude of the warming trend varies depending on the datasets and length of the analyzed period. The warming trend has been more evident since 1980 and has further enhanced since 2000. Long-term trends in climate and hydrology are assessed. Various studies have reported an intensification of the hydrological cycle and a lengthening of the dry season in the southern Amazon. Changes in floods and droughts, mainly due to natural climate variability and land use change, are also assessed. For instance, in the first half of the 20th century, extreme flood events occurred every 20 years. Since 2000, there has been one severe flood every four years. During the last four decades, the northern Amazon has experienced enhanced convective activity and rainfall, in contrast to decreases in convection and rainfall in the southern Amazon. Climate change in the Amazon will have impacts at regional and global scales. Significant reductions in rainfall are projected for the eastern Amazon.
Variabilidade de longo prazo, extremos e mudanças de temperatura e hidrometeorologia na Região Amazônica: Uma revisão
Keywords: Climate change; climate models; drought; floods; land-use change; moisture transport; warming